cau h
5[sinx + (cos3x + sin3x)/(1 + 2sin2x) ] = cos2x + 3 với x ∈ (0 ; 2π)
đk: sin2x ≠ -1/2 <=> x ≠ -π/12 + kπ (k ∈ Z) hoặc x ≠ 13π/12 + kπ (k ∈ Z)
pt ⇔ 5(sinx + 2.sinx.sin2x + cos3x + sin3x) = (cos2x + 3)(1 + 2sin2x)
⇔ 5(sinx + cosx - cos3x + cos3x + sin3x) = (cos2x + 3)(1 + 2sin2x)
⇔ 5(sinx + sin3x + cosx) = (cos2x + 3)(1 + 2sin2x)
⇔ 5(2sin2x.cosx + cosx) = (cos2x + 3)(1 + 2sin2x)
⇔ 5.cosx.(2sin2x + 1) = (cos2x + 3)(1 + 2sin2x)
⇔ 5cosx = cos2x + 3
⇔ 2cos²x - 5cosx + 2 = 0
⇔ (2cosx - 1)(cosx - 2) = 0
⇔ cosx = 1/2 , do cosx ≤ 1 --> cosx - 2 < 0
⇔ x = ± π/3 + k2π (k ∈ Z) .. thỏa mãn đk
Do x ∈ (0 ; 2π)
TH1: x = π/3 + k2π (k ∈ Z)
có: 0 ≤ π/3 + k2π ≤ 2π --> -1/6 ≤ k ≤ 5/6 mà k ∈ Z --> k = 0
--> x = π/3
TH2: x = -π/3 + k2π (k ∈ Z)
có: 0 ≤ -π/3 + k2π ≤ 2π --> 1/6 ≤ k ≤ 7/6 mà k ∈ Z --> k = 1
--> x = 5π/3
Vậy pt đã cho có 2 nghiệm là x = π/3 và x = 5π/3